Optimizing the implementation of lung cancer screening in Scotland: Focus group participant perspectives in the LUNGSCOT study. (20th October 2022) - Cavers, Debbie; Nelson, Mia; Rostron, Jasmin; Robb, Kathryn A.; Brown, Lynsey R.; Campbell, Christine; Akram, Ahsan R.; Dickie, Graeme; Mackean, Melanie; van Beek, Edwin J. R.; Sullivan, Frank; Steele, Robert J.; et al.
Abstract: Introduction: Targeted lung cancer screening is effective in reducing lung cancer and all‐cause mortality according to major trials in the United Kingdom and Europe. However, the best ways of implementing screening in local communities requires an understanding of the population the programme will serve. We undertook a study to explore the views of those potentially eligible for, and to identify potential barriers and facilitators to taking part in, lung screening, to inform the development of a feasibility study. Methods: Men and women aged 45–70, living in urban and rural Scotland, and either self‐reported people who smoke or who recently quit, were invited to take part in the study via research agency Taylor McKenzie. Eleven men and 14 women took part in three virtual focus groups exploring their views on lung screening. Focus group transcripts were transcribed and analysed using thematic analysis, assisted by QSR NVivo. Findings: Three overarching themes were identified: (1) Knowledge, awareness and acceptability of lung screening, (2) Barriers and facilitators to screening and (3) Promoting screening and implementation ideas . Participants were largely supportive of lung screening in principle and described the importance of the early detection of cancer. Emotional and psychological concerns as well as system‐level and practical issues were discussed as posing barriers and facilitators to lung screening. Conclusions: Understanding the views of people potentially eligible for a lung health check can usefully inform the development of a further study to test the feasibility and acceptability of lung screening in Scotland. Patient or Public Contribution: The LUNGSCOT study has convened a patient advisory group to advise on all aspects of study development and implementation. Patient representatives commented on the focus group study design, study materials and ethics application, and two representatives read the focus group transcripts.